PIPERANTHA:INOVASI TERAPI KOMBINASI EKSTRAK DAUN SALAM (EUGENIA POLYANTHA) DAN SIRIH MERAH (PIPER CROCATUM) TERHADAP PENINGKATAN AKTIVITAS FAS/FAS-L PADA REGRESI PERTUMBUHAN KANKER SERVIKS SECARA IN VITRO - Wicaksono, Firman Mulyo; Sari, Desie Suci Permata; Sekti, Beta Herilla; Sari, Yitania; Natalia, Ellen; Lyrawati, Diana; Febriyanti, Alifia Putri (Program Kreativitas Mahasiswa - Penelitian, 2013)
In this study, we evaluated Eugenia polyantha and Piper crocatum leaves alone and in combination for their anti-cancer properties on HeLa cells. The extraction method by using soxhlet and maceration. The phytochemical constituents of extract were evaluated by qualitative and quantitative analysis. The anti-cancer property and mechanism of the extract were evaluated by its effect on cell viability and apoptosis. Total flavonoids content was higher in maceration than soxhlet extracts. Single extracts of Eugenia polyantha alone or Piper crocatum showed better anti-cancer activity than their combination. However, Eugenia polyantha extracts showed better anti-cancer activity than Piper crocatum extracts.Â Keywords : HeLa cell, Eugenia polyantha, Piper crocatum, single, combination